Pulmonary function after lung tumor stereotactic ablative radiotherapy depends on regional ventilation within irradiated lung. Issue 2 (May 2017) - Binkley, Michael S.; King, Martin T.; Shrager, Joseph B.; Bush, Karl; Chaudhuri, Aadel A.; Popat, Rita; Gensheimer, Michael F.; Maxim, Peter G.; Henry Guo, H.; Diehn, Maximilian; Nair, Viswam S.; Loo, Billy W.
Abstract: Purpose: To determine if regional ventilation within irradiated lung volume predicts change in pulmonary function test (PFT) measurements after stereotactic ablative radiotherapy (SABR) of lung tumors. Methods: We retrospectively identified 27 patients treated from 2007 to 2014 at our institution who received: (1) SABR without prior thoracic radiation; (2) pre-treatment 4-dimensional computed tomography (4-D CT) imaging; (3) pre- and post-SABR PFTs <15 months from treatment. We defined the ventilation ratio (VR20BED3 ) as the quotient of mean ventilation (mean Jacobian-based per-voxel volume change on deformably registered inhale/exhale 4-D CT phases) within the 20 Gy biologically effective dose ( α / β = 3 Gy) isodose volume and that of the total lung volume (TLV). Results: Most patients had moderate to very severe COPD by GOLD criteria ( n = 19, 70.1%). Higher VR20BED3 significantly predicted worse change in Forced Expiratory Volume/s normalized by baseline value (ΔFEV1 /FEV1pre, p = 0.04); n = 7 had VR20BED3 > 1 (high regional ventilation) and worse ΔFEV1 /FEV1pre (median = −0.16, range = −0.230 to −0.20). Five had VR20BED3 < 1 (low regional ventilation) and improved ΔFEV1 /FEV1pre (median = 0.13, range = 0.07 to 0.20). In a multivariable linear model, increasing VR20BED3 and time to post-SABR PFT predicted decreasing ΔFEV1 /FEV1pre ( R 2 = 0.25, p = 0.03). Conclusions: After SABR to high versus low functioning lung regions, we found worsened or improved global pulmonary function, respectively. If pre-SABR VR20BED3 is validated as a predictor of eventual post-SABR PFT in larger studies, it may be used for individualized treatment planning to preserve or even improve pulmonary function after SABR.